Rancang Bangun Aplikasi Absensi SD Negeri 19 Pasar Cubadak Berbasis Web - Hayatun Nupus; Denny Kurniadi; Ahmaddul Hadi; Rizkayeni Marta (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Attendance is an essential component of school management that serves as both proof of presence and a basis for evaluating the discipline of teachers, students, and staff. The manual attendance system that is still widely used often leads to several issues, such as delayed data recapitulation, potential attendance manipulation, and low recording accuracy. This study aims to design and develop a web-based attendance application at SD Negeri 19 Pasar Cubadak by integrating geolocation, timestamp, and face recognition features as attendance validation tools. The research method employed is the Research and Development (R&D) approach using the Waterfall software development model, which includes the stages of requirements analysis, system design, implementation, and testing. The application was developed using the Laravel framework with PHP and JavaScript programming languages and a MySQL database. The results show that the web-based attendance application can record attendance in real-time, automatically validate user location and identity, and generate accurate and transparent attendance reports. The User Acceptance Test (UAT) results indicate that the system is user-friendly, improves recapitulation efficiency, and assists the principal in objectively monitoring school members’ discipline. Therefore, this application is expected to serve as a modern solution to enhance the effectiveness of attendance administration in primary education environments.